Preparation method of Cr < 3 + >-loaded phenolic resin-based catalyst and application of Cr < 3 + >-loaded phenolic resin-based catalyst in preparation of 5-hydroxymethylfurfural
The Cr3+ phenolic resin-based catalyst was prepared by sol-gel method, and applied to glucose conversion to prepare HMF, which solved the problems of low HMF yield and difficult catalyst recovery in the prior art, and achieved efficient and environmentally friendly HMF preparation and catalyst stability and significantly improved recycling.
Patent Information
- Application Number
- CN202411269882.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2024-12-13
AI Technical Summary
When using raw materials such as glucose, sucrose, starch, etc. to prepare 5-hydroxymethylfurfural (HMF), there are problems such as low HMF yield, high cost and complex process, and the strong acid catalyst used is difficult to recover and the environmental pollution is serious. Difficult to regenerate catalysts.
The supported Cr3+ phenolic resin-based catalyst was prepared by the sol-gel method and applied to glucose catalytic conversion to prepare HMF. By reacting with dimethyl sulfoxide and saturated sodium chloride solution, efficient catalysis and easy catalyst recovery.
Improve the yield and catalytic activity of HMF, the glucose conversion rate can reach 83-100%, the yield of HMF can reach 50-69%, the catalyst has good stability, and it still maintains high activity after multiple reuses, and the process is more environmentally friendly and simple. .
Smart Images

Figure BDA0005038391090000041 
Figure BDA0005038391090000051 
Figure BDA0005038391090000061
Abstract
Description
Technical Field
[0001] The present invention relates to the field of biomass energy conversion, in particular to loading Cr 3+ A preparation method of a phenolic resin-based catalyst and application thereof in the preparation of 5-hydroxymethylfurfural. Background Art
[0002] The rapid depletion of fossil fuels has led to an increase in the use of renewable energy worldwide. Five-carbon and six-carbon sugars from biomass are considered to be the most ideal substitutes for fossil resources due to their sustainable and renewable properties. Among the numerous biomass-derived compounds, 5-hydroxymethylfurfural (HMF) is considered to be the most attractive and promising platform compound. The molecular structure of HMF has two unsaturated double bonds, a carbonyl group and an ether bond. This unique chemical structure can be used to prepare a variety of chemical substances with important commercial value through reactions such as oxidation, hydrogenation and amination. At present, HMF can be obtained by acid hydrolysis of fructose, glucose, sucrose, starch and sugar oligomers. Due to the high reaction barrier of glucose isomerization, oligosaccharides such as sucrose and starch need to be hydrolyzed into monosaccharides before isomerization, and the yield of HMF is lower. Therefore, industrial production mainly uses expensive fructose as raw material to produce HMF, while the preparation of HMF using glucose, sucrose and starch as raw materials can significantly reduce costs, which is more attractive and challenging. At present, the process of synthesizing HMF using glucose, sucrose and starch as raw materials has the problems of low HMF yield, high cost and complex process due to the generation of a large number of by-products.
[0003] The acid catalysts for synthesizing HMF mainly include inorganic acids such as hydrochloric acid, sulfuric acid, phosphoric acid, oxalic acid, p-toluenesulfonic acid, etc. Strong acid catalysts are difficult to recycle, corrode equipment, and cause serious environmental pollution. It is also difficult to regenerate the catalyst.
[0004] Homogeneous catalysts are not convenient for product separation, recycling is cumbersome, and the reaction usually takes too long. For example, XIAO et al. [XIAO, et al. Efficient conversion of cellulose into biofuel precursor 5-hydroxymethylfurfural in dimethyl sulfoxide–ionic liquid mixtures] used AlCl3 as a catalyst and established a method for efficiently converting cellulose into 5-hydroxymethylfurfural in a DMSO / ionic liquid mixture. After reacting at 150°C for 9 hours in a mixed solvent of DMSO / ionic liquid (10wt.%), a 54.9% HMF yield was obtained, but there was a problem of long reaction time. At present, significant progress has been made in the conversion of fructose, glucose, cellulose, starch and biomass raw materials into HMF using heterogeneous catalysts such as zeolites, molecular sieves, ion exchange resins and metal oxides as catalysts. For example, Mercedes Moreno-Recio et al. [Mercedes Moreno-Recio, and Lewis acid ZSM-5zeolites for the catalytic dehydration of glucose into 5-hydroxymethylfurfural] prepared molecular sieve (NH4-ZSM-5), with H2O / MIBK as solvent, after adding NaCl, NH4-ZSM-5 reacted at 195℃ for 30min, the HMF yield was 42%. WANG et al. [WANG, et al. Efficient conversion of glucose into 5-HMF catalyzed by lignin-derived mesoporous carbon solidacid in abiphasic system] used alkaline lignin as carbon source and KCl as salt template, prepared lignin-derived mesoporous carbon solid acid catalyst by high temperature carbonization and subsequent sulfonation treatment. Under optimized reaction conditions, with NaCl-THF as solvent system, the reaction was carried out at 160℃ for 2.5h, and the HMF yield was 57.8%, but there was a problem of generating a large amount of toxic wastewater when preparing the catalyst.
[0005] Resin-type solid acid catalysts have the advantages of water resistance and low active temperature, and are suitable for various condensation reactions and dehydration reactions. At present, there are many commercial resin-type solid acid catalysts. Publication No. CN110560161A discloses a preparation method of a sulfonated phenolic resin type solid acid catalyst, which uses p-hydroxybenzenesulfonic acid, phenol and polyformaldehyde to carry out polycondensation reaction by a one-step polycondensation method to prepare a sulfonated phenolic resin type solid acid catalyst with a cross-linked structure. The catalyst is applied to glycerol esterification reaction, has the advantages of simple preparation process and good stability, but the catalyst uses phenol and polyformaldehyde, has poor safety and is not environmentally friendly.
[0006] At present, there is no report on the efficient catalytic conversion of biomass into HMF using a resin-type solid acid catalyst loaded with metal ions. 3+ Phenolic resin-based catalyst is used in the catalytic conversion of glucose to prepare HMF. Compared with other solid acid catalysts, it has high catalytic activity, easy catalyst recovery, and the HMF yield does not decrease after multiple reuses of the catalyst, so it has broad application prospects. Summary of the invention
[0007] The technical problem to be solved by the present invention is to provide a load Cr 3+ A method for preparing a phenolic resin-based catalyst, and applying the catalyst to catalytically convert glucose to efficiently prepare HMF.
[0008] In order to achieve the above object, the present invention adopts the following technical solutions:
[0009] A load Cr 3+ The preparation method of the phenolic resin-based catalyst comprises the following steps:
[0010] (1) dissolving F127, ammonia water, tannic acid and formaldehyde solution in water, and obtaining a poly (tannic acid) oligomer (PTF) solution after sufficient reaction;
[0011] (2) adding chromium trichloride hexahydrate to the poly(tannic acid) oligomer solution obtained in step (1), and obtaining a metal / polymer composite material after sufficient reaction;
[0012] (3) The metal / polymer composite material obtained in step (2) is subjected to hydrothermal treatment, washed, centrifuged and dried to obtain a Cr-loaded 3+ Phenolic resin based catalyst (Cr-PTF).
[0013] Furthermore, in step (1), the mass ratio of F127 to tannic acid is 2:3-4:1, and the pH of the reaction solution is controlled at 9-11; the preferred result is that the mass ratio of F127 to tannic acid is 1:1.
[0014] Furthermore, in step (2), the mass ratio of the chromium chloride hexahydrate to tannic acid is 1:1-7:2, and the preferred ratio is 3:1.
[0015] Furthermore, in step (3), the hydrothermal temperature is 100-200°C, the hydrothermal time is 4h, the rotation speed during centrifugation is 7000-9000r / min, and the drying temperature is 60-90°C; the preferred result is: the hydrothermal temperature is 160°C, the rotation speed during centrifugation is 9000r / min, and the drying temperature is 70°C.
[0016] The load Cr 3+ The application of phenolic resin-based catalyst is to utilize the loaded Cr 3+ Phenolic resin-based catalyst catalyzes the conversion of glucose into 5-hydroxymethylfurfural. It includes using glucose as a raw material, a mixture of dimethyl sulfoxide and a saturated sodium chloride solution as a solvent, and adding a Cr-loaded 3+ The phenolic resin-based catalyst is reacted, and after the reaction is completed, it is filtered and the catalyst is recovered for reuse.
[0017] Furthermore, the volume ratio of the dimethyl sulfoxide to the saturated sodium chloride solution is 17:3-19:1, and the preferred result is 9:1; the amount of solvent used for every 0.15 g of glucose is 20 mL.
[0018] Furthermore, the glucose and the loaded Cr 3+ The mass ratio of the phenolic resin-based catalyst is 3:1.5-3:2.5, and the preferred result is 2:1.
[0019] Furthermore, the reaction temperature is 160-180°C, and the reaction time is 2-4h; the preferred result is that the reaction temperature is 180°C, and the reaction time is 3h.
[0020] The technical effects of the present invention are as follows:
[0021] (1) The loaded Cr prepared by the sol-gel method in the present invention 3+ Phenolic resin-based catalyst. Compared with existing methods, it is relatively environmentally friendly and the catalyst preparation steps are simpler.
[0022] (2) The inventors of this application creatively discovered that the load Cr 3+ The phenolic resin-based catalyst is used in the catalytic conversion of glucose to prepare HMF. Compared with other solid acid catalysts, it has a very high catalytic activity (the glucose conversion rate can reach 83-100%), the HMF yield can reach 50-69%, and it has good stability. It can still maintain a high catalytic activity after multiple cycles of use, and the catalyst is easy to recover, which has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The loaded Cr prepared in Examples 1, 3, and 5 3+ XRD pattern of phenolic resin-based catalyst (Cr-PTF).
[0024] Figure 2 The loaded Cr prepared in Example 5 3+ SEM image of phenolic resin-based catalyst (Cr-PTF). DETAILED DESCRIPTION
[0025] The present invention will be further described below in conjunction with embodiments.
[0026] Embodiment 1:
[0027] This embodiment loads Cr 3+ The preparation method of phenolic resin based catalyst (Cr-PTF) is as follows:
[0028] (1) Weigh 0.2 g of F127 into a 100 mL sample bottle, add 50 mL of deionized water and stir to dissolve it, to prepare an F127 solution; add 0.5 mL of ammonia water to the F127 solution to make the solution alkaline, add 0.2 g of tannic acid and 0.4 mL of formaldehyde solution and stir to dissolve it, the pH of the reaction solution is controlled at 9-11, and after sufficient reaction, a solution containing poly (tannic acid) oligomers is obtained.
[0029] (2) adding 0.2 g of chromium trichloride hexahydrate to the poly(tannic acid) oligomer solution obtained in step (1) and stirring to allow the mixture to react fully to obtain a metal / polymer composite material.
[0030] (3) Heat at 160°C for 4 h, cool in a water bath to room temperature, and finally remove the loaded Cr 3+ The phenolic resin-based catalyst was washed with distilled water until neutral, the solution was centrifuged at a speed of 9000 r / min, and the separated product was dried in an oven at 70°C for 12 h; the dried solid was ground into a uniform powder with a mortar to obtain the loaded Cr 3+ Phenolic resin based catalyst.
[0031] Preparation of HMF: Weigh 0.15 g of glucose, 0.075 g of catalyst, 18 mL of dimethyl sulfoxide (DMSO), and 2 mL of saturated sodium chloride solution, mix them in a high-pressure reactor, seal it, put it in an oven and heat it to 180°C for 3 hours, and after the reaction is completed, cool the reactor to room temperature in a water bath. The conversion rate of glucose in this example was measured separately, and the yield of HMF was measured by high-performance liquid chromatography, and the final glucose conversion rate was 98%, and the HMF yield was 57%.
[0032] Embodiment 2-6:
[0033] Example Loading Cr3+ The preparation method of phenolic resin based catalyst is as follows:
[0034] (1) Same as Example 1.
[0035] (2) adding 0.3 g, 0.4 g, 0.5 g, 0.6 g, and 0.7 g of chromium trichloride hexahydrate to the poly(tannic acid) oligomer solution obtained in step (1), respectively, and stirring to allow the mixture to react fully to obtain a metal / polymer composite material.
[0036] (3) Heat at 160°C for 4 h, cool in a water bath to room temperature, and finally remove the loaded Cr 3+ The phenolic resin-based catalyst was washed with distilled water until neutral, the solution was centrifuged at a speed of 9000 r / min, and the separated product was dried in an oven at 70°C for 12 h; the dried solid was ground into a uniform powder with a mortar to obtain the loaded Cr 3+ Phenolic resin based catalyst.
[0037] Preparation of HMF: Same as Example 1.
[0038] The conversion rates of glucose in Examples 2-6 were measured respectively, and the yields of HMF were measured by high performance liquid chromatography. The results are shown in Table 1.
[0039] Table 1: Glucose conversion and HMF yield of catalysts with different metal addition amounts.
[0040]
[0041] Embodiment 7-11:
[0042] Example Loading Cr 3+ The preparation method of phenolic resin based catalyst is as follows:
[0043] (1) Weigh 0.2 g of F127 into a 100 mL sample bottle, add 50 mL of deionized water and stir to dissolve it to prepare an F127 solution; add 0.5 mL of ammonia water to the F127 solution to make the solution alkaline, add 0.05 g, 0.1 g, 0.15 g, 0.25 g, 0.3 g of tannic acid and 0.4 mL of formaldehyde solution respectively, stir to dissolve it, control the pH of the reaction solution to 9-11, and obtain a solution containing poly (tannic acid) oligomers after sufficient reaction.
[0044] (2) adding 0.6 g of chromium trichloride hexahydrate to the poly(tannic acid) oligomer solution obtained in step (1) and stirring to allow the mixture to react fully to obtain a metal / polymer composite material.
[0045] (3) Heat at 160°C for 4 h, cool in a water bath to room temperature, and finally remove the loaded Cr 3+The phenolic resin-based catalyst was washed with distilled water until neutral, the solution was centrifuged at a speed of 8000 r / min, and the separated product was dried in an oven at 80°C for 12 h; the dried solid was ground into a uniform powder with a mortar to obtain a loaded Cr 3+ Phenolic resin based catalyst.
[0046] Preparation of HMF: Same as Example 1.
[0047] The conversion rates of glucose in Examples 7-11 were measured respectively, and the yields of HMF were measured by high performance liquid chromatography. The results are shown in Table 2.
[0048] Table 2: Conversion rate of glucose and yield of HMF with different tannic acid addition amounts.
[0049] Example Tannic acid addition amount (g) Glucose conversion rate (%) HMF yield (%) 7 0.05 100 51 8 0.1 100 56 9 0.15 100 59 5 0.2 100 69 10 0.25 100 58 11 0.3 100 51
[0050] Embodiment 12-16:
[0051] Example Loading Cr 3+ The preparation method of phenolic resin based catalyst is as follows:
[0052] (1) Same as Example 1.
[0053] (2) adding 0.6 g of chromium trichloride hexahydrate to the poly(tannic acid) oligomer solution obtained in step (1) and stirring to allow the mixture to react fully to obtain a metal / polymer composite material.
[0054] (3) Heat the mixture at 100°C, 120°C, 140°C, 180°C, and 200°C for 4 h, cool it to room temperature in a water bath, and finally remove the loaded Cr 3+ The phenolic resin-based catalyst was washed with distilled water until neutral, the solution was centrifuged at a speed of 9000 r / min, and the separated product was dried in an oven at 70°C for 12 h; the dried solid was ground into a uniform powder with a mortar to obtain the loaded Cr 3+ Phenolic resin based catalyst.
[0055] Preparation of HMF: Same as Example 1.
[0056] The conversion rates of glucose in Examples 12-16 were measured respectively, and the yields of HMF were measured by high performance liquid chromatography. The results are shown in Table 3.
[0057] Table 3: Glucose conversion and HMF yield at different hydrothermal temperatures of different catalysts.
[0058]
[0059] Embodiment 17-19:
[0060] Example Loading Cr3+ The preparation method of phenolic resin based catalyst is as follows:
[0061] (1) Same as Example 1.
[0062] (2) adding 0.6 g of chromium trichloride hexahydrate to the poly(tannic acid) oligomer solution obtained in step (1) and stirring to allow the mixture to react fully to obtain a metal / polymer composite material.
[0063] (3) Same as Example 1.
[0064] Preparation of HMF: Weigh 0.15 g of glucose, 0.09 g, 0.1 g, and 0.125 g of catalysts respectively, 18 mL of DMSO, and 2 mL of saturated sodium chloride, mix them in a high-pressure reactor, seal it, and heat it in an oven to 180°C for 3 hours. After the reaction is completed, cool the reactor to room temperature in a water bath and obtain HMF after centrifugation.
[0065] The conversion rates of glucose in Examples 17-19 were measured respectively, and the yields of HMF were measured by high performance liquid chromatography. The results are shown in Table 4.
[0066] Table 4: Effect of catalyst addition on glucose conversion and HMF yield.
[0067]
[0068] Embodiment 20-21:
[0069] (1) Same as Example 1.
[0070] (2) adding 0.6 g of chromium trichloride hexahydrate to the poly(tannic acid) oligomer solution obtained in step (1) and stirring to allow the mixture to react fully to obtain a metal / polymer composite material.
[0071] (3) Same as Example 1.
[0072] Preparation of HMF: Weigh 0.15 g of glucose, 0.075 g of catalyst, 18 mL of DMSO, and 2 mL of saturated sodium chloride, mix them in a high-pressure reactor, seal it, put it in an oven and heat it to 180°C for 2 h or 4 h. After the reaction is completed, cool the reactor to room temperature in a water bath and obtain HMF after centrifugation.
[0073] The conversion rates of glucose in Examples 20-21 were measured respectively, and the yields of HMF were measured by high performance liquid chromatography. The results are shown in Table 5.
[0074] Table 5: Effect of reaction time on glucose conversion and HMF yield.
[0075]
[0076] Embodiment 22-23:
[0077] (1) Same as Example 1.
[0078] (2) adding 0.6 g of chromium trichloride hexahydrate to the poly(tannic acid) oligomer solution obtained in step (1) and stirring to allow the mixture to react fully to obtain a metal / polymer composite material.
[0079] (3) Same as Example 1.
[0080] Preparation of HMF: Weigh 0.15 g of glucose, 0.075 g of catalyst, 18 mL of DMSO, and 2 mL of saturated sodium chloride, mix them in a high-pressure reactor, seal it, and heat it in an oven to 160°C or 170°C for 3 hours. After the reaction is completed, cool the reactor to room temperature in a water bath and obtain HMF after centrifugation.
[0081] The conversion rates of glucose in Examples 22-23 were measured respectively, and the yields of HMF were measured by high performance liquid chromatography. The results are shown in Table 6.
[0082] Table 6: Effect of reaction temperature on glucose conversion and HMF yield.
[0083]
[0084] Embodiment 24-25:
[0085] (1) Same as Example 1.
[0086] (2) adding 0.6 g of chromium trichloride hexahydrate to the poly(tannic acid) oligomer solution obtained in step (1) and stirring to allow the mixture to react fully to obtain a metal / polymer composite material.
[0087] (3) Heat at 160°C for 4 h, cool in a water bath to room temperature, and finally remove the loaded Cr 3+ The phenolic resin-based catalyst was washed with distilled water until neutral, the solution was centrifuged at a speed of 7000 r / min, and the separated product was dried in an oven at 60°C for 12 h; the dried solid was ground into a uniform powder with a mortar to obtain the loaded Cr 3+ Phenolic resin based catalyst.
[0088] Preparation of HMF: Weigh 0.15 g of glucose, 0.075 g of catalyst, DMSO: saturated sodium chloride volume ratio of 17:3 or 19:1, and a total solvent volume of 20 ml, mix them and put them in a high-pressure reactor. After sealing, put it in an oven and heat it to 180°C for 3 hours. After the reaction is completed, cool the reactor to room temperature in a water bath and obtain HMF after centrifugation.
[0089] The conversion rates of glucose in Examples 24-25 were measured respectively, and the yields of HMF were measured by high performance liquid chromatography. The results are shown in Table 7.
[0090] Table 7: Conversion rate of glucose and yield of HMF with different reaction solvent ratios.
[0091] Example DMSO: saturated sodium chloride Glucose conversion rate (%) HMF yield (%) 24 17:3 100 51 5 9:1 100 69 25 19:1 100 51
[0092] Table 8: Catalyst recycling results of Example 5
[0093]
Claims
1. A load Cr 3+ A method for preparing a phenolic resin-based catalyst, It is characterized in that The following steps are involved: (1) dissolving F127, ammonia water, tannic acid and formaldehyde solution in water, and reacting them sufficiently to obtain a solution containing poly (tannic acid) oligomers; (2) adding chromium trichloride hexahydrate to the poly(tannic acid) oligomer solution obtained in step (1), and obtaining a metal / polymer composite material after sufficient reaction; (3) The metal / polymer composite material obtained in step (2) is subjected to hydrothermal treatment, washed, centrifuged and dried to obtain a Cr-loaded 3+ Phenolic resin based catalyst.
2. A loaded Cr according to claim 1 3+ A method for preparing a phenolic resin-based catalyst, Features: In step (1), the mass ratio of F127 to tannic acid is 2:3-4:1, and the pH of the reaction solution is controlled at 9-11.
3. A loaded Cr according to claim 1 3+ A method for preparing a phenolic resin-based catalyst, Features: In step (2), the mass ratio of chromium chloride hexahydrate to tannic acid is 1:1-7:
2.
4. A loaded Cr according to claim 1 3+ A method for preparing a phenolic resin-based catalyst, Features: In step (3), the hydrothermal temperature is 100-200°C, the hydrothermal time is 4 hours, the rotation speed during centrifugal separation is 7000-9000r / min, and the drying temperature is 60-90°C.
5. A loaded Cr as claimed in claim 1 3+ Application of phenolic resin based catalysts, Features: Using the load Cr 3+ Phenolic resin-based catalysts were used to catalyze the conversion of glucose into 5-hydroxymethylfurfural.
6. The use according to claim 5, Features: Glucose was used as raw material, a mixture of dimethyl sulfoxide and saturated sodium chloride solution was used as solvent, and Cr-loaded 3+ The phenolic resin-based catalyst is reacted, and after the reaction is completed, it is filtered and the catalyst is recovered for reuse.
7. The use according to claim 6, Features: The volume ratio of the dimethyl sulfoxide to the saturated sodium chloride solution is 17:3-19:1; the amount of solvent used for every 0.15 g of glucose is 20 mL.
8. The use according to claim 6, Features: The glucose and Cr loading 3+ The mass ratio of the phenolic resin-based catalyst is 3:1.5-3:2.
5.
9. The use according to claim 6, Features: The reaction temperature is 160-180°C and the reaction time is 2-4h.
